Tindak Ilokusi dalam Debat Capres Ri Pemilu 2019 dan Korelasinya dengan Prinsip Kesantunan - Tuty Ayudatussholiha (Mabahits : Jurnal Hukum Keluarga Islam, 2020)
Political debate is one of the means to grab people's attention, and sometimes it does not escape the condition of bringing down opponents through the arguments put forward. Such an argument must of course be packaged with good language use skills, because apart from being needed to reduce the opponent's value, the argument is also needed to increase self-worth. To find out the ability to use language possessed by Indonesian presidential candidates, it can be done by identifying the types of illocutionary acts contained in the 2019 Indonesian presidential candidate debates and how they correlate with politeness principles. The theory adopted in this research is Searle's speech act theory and the politeness theory which has been summarized by Leech. To achieve the final result, this research needs to go through three stages, namely the stage of collecting data using the listening method and note-taking technique, the data analysis stage using the pragmatic equivalent method and the comparison-equalizing technique, and finally the stage of presenting the analysis results using orthographic text. The results of the study show that in the 2019 Indonesian presidential candidate debate forum, Jokowi mostly uses speech with the 'report' function, this is because Jokowi has experience leading a country, so he has things to report, while Prabowo does not have experience leading a country. and is intending to run for president, so the speeches conveyed are mostly in the form of 'expressing opinions', 'proposing', 'criticizing', and 'promising something'. It is these statements that make Prabowo dominate the application of the politeness principle. Even so, the two presidential candidates were able to process their arguments well.